A Comprehensive Primer on Transgender Health in India - Kattamreddy Ananth Rupesh; Anirudh Suseel Nalumaru; Mohit Kumar Moses T; Keertan Adarsh Bhagavathula; Keerthana Chunduru; Naga Tejaswi Surla; Manasa Marada; Alekhya Marina (National Board of Examinations Journal of Medical Sciences, 2023)
Background: Transgender health care deals with the prevention, diagnosis, and treatment of physical and mental health conditions along with sex reassignment surgeries and hormonal therapies pertaining to transgender population. Despite the numerous positive developments and efforts made for the welfare of transgender individuals, the plight of these people is yet very dire across the globe. The limited access to specialized healthcare services further exacerbates their predicament due to associated social stigma. Objectives: This mini-review delves into several crucial aspects concerning transgender healthcare in India. It focuses on the evolution of intersex states at birth and during development in general, the sociocultural challenges faced by transgender people within healthcare institutions, the ethical dilemmas entwined in their care and the need for more gender inclusive medical curriculum. Results: The current state of knowledge on transgender health among healthcare providers is inadequate and there is a strong need for revision of medical curriculum to suit the needs of transgenders. Matters such as the prevalence of transgender identity, gender dysphoria, sociocultural aspects of disorders in sexual development (DSD), and hormonal and surgical therapies for sex reassignment are explored, emphasizing the importance of gender-affirming surgeries in supporting gender identity. However, concerns regarding coerced surgeries, quack interventions, and lack of specialized medical expertise in treating transgenders are raised. Conclusions: Establishing specialized transgender clinics and revising medical curricula, while addressing ethical, legal, and sociocultural challenges of transgender individuals, is vital for improving transgender healthcare in India.